Sistem Pakar Mendiagnosis Penyakit Mata Manusia Menggunakan Metode Fuzzy Mamdani - Dwinita Arwidiyarti; Juhartini, Juhartini; Surni Erniwati (LPPM Universitas Dinamika Bangsa, 2024)
The medical field has utilized technology in an effort to improve better services in diagnosing diseases, one of which is eye disease in humans. Because the eye is one of the five senses that is important to interact with the surrounding environment. The doctor's work is very busy and busy resulting in delays in serving the community. To overcome this, an expert system is needed to assist patients in diagnosing early eye disease, so that patients can find out the eye disease they are suffering from and its severity. This study discusses the creation of an expert system using the fuzzy mamdani concept to diagnose eye disease. The Fuzzy Mamdani method has been successfully implemented into an expert system for diagnosing eye diseases. This expert system uses the fuzzy mamdani method for diagnosing eye diseases which can provide fast diagnosis results along with the level of certainty for each disease. Expert systems can diagnose diseases based on the trust value of the disease using the Fuzzy Mamdani formula. From the results of the diagnosis calculations performed by the system, it can be seen that the accuracy of the system diagnosis with doctors reaches 93.3%